Návrh technologie výroby plastového emblému automobilu - Bombera, Mojmír (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2013)
Projekt, vypracovaný v rámci inženýrského studia oboru 2307 předkládá návrh technologie výroby plastového emblému automobilu. Na základě literární studie problematiky byly porovnány různé technologie vhodné pro výrobu. Jde o tlakového lití slitiny hliníku a technologii vstřikování plastů. Plastový výlisek je následně pokoven, aby bylo docíleno tzv. metalického vzhledu. Součástí projektu je návrh vstřikovací formy včetně technologických výpočtů a ekonomický rozbor.

The project elaborated in scope of engineering studies branch 2307. The project is submitting design of production technology of car emblem. Different manufacturing technologies have been compared based on study of technical literature. Most suitable technologies have been chosen such as pressure die casting, especially aluminum alloys and plastic injection molding. Plastic part is metal plated afterwards in order to get desired metal look. Part of this project is injection molding tool design inclusive technical, technological and economic analysis.
Design of manufacturing technology for plastic car emblem
Keywords: Plasty; vstřikování plastů; pokovování; tlakové lití kovů; Plastics; injection molding; metal plating; pressure die casting